1982
DOI: 10.2172/5108667
|View full text |Cite
|
Sign up to set email alerts
|

PNL technical review of pressurized thermal-shock issues. [PWR]

Abstract: Pacific Northwest laboratory (PNL) was asked to develop and recommend a regulatory position that the Nuclear Regulatory Commission (NRC) should adopt regarding the ability of reactor pressure vessels to withstand the effects of pressurized thermal shock (PTS). Licensees of eight pressurized water reactors provided NRC with estimates of remaining effective full power years before corrective actions would be required to prevent an unsafe operating condition. PNL reviewed these responses and the results of suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1983
1983

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Certain ORNL tests have shown that a rapid growth in crack length could transform a crack of relatively small aspect ratio into a long flaw. Accordingly, the acceptance criteria proposed by PNL in NUREG-2837 (6) recommended that the 6:1 postulated flaw be treated as a long axial or circumferential flaw once crack growth initiates.…”
Section: Crack Shapementioning
confidence: 99%
“…Certain ORNL tests have shown that a rapid growth in crack length could transform a crack of relatively small aspect ratio into a long flaw. Accordingly, the acceptance criteria proposed by PNL in NUREG-2837 (6) recommended that the 6:1 postulated flaw be treated as a long axial or circumferential flaw once crack growth initiates.…”
Section: Crack Shapementioning
confidence: 99%